RECURRENT BULLOUS ERYTHEMA MULTIFORME SECONDARY TO HERPES SIMPLEX INFECTION IN AN 18-YEAR-OLD MALE: A CASE STUDY. - Abraham Mukalazi; KATUNGI (Student's Journal of Health Research Africa)
Introduction